2021
DOI: 10.1002/eat.23583
|View full text |Cite
|
Sign up to set email alerts
|

Shame and eating disorders symptoms: A meta‐analysis

Abstract: Objective: Numerous empirical studies and theoretical models posit that shame is a common experience among individuals across the eating disorder spectrum. In this study we aim to investigate the association between shame and eating disorders symptoms using a meta-analytical approach.Method: In this meta-analysis, we synthesized findings from 195 studies to examine the proposed association between shame and eating disorders symptoms. We looked at the associations with both general eating disorders symptoms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 241 publications
(93 reference statements)
1
20
0
Order By: Relevance
“…However, engaging in ED behaviors to cope with shame may eventually increase shame (e.g., regarding eating, shape and weight), setting up a vicious cycle [ 52 ]. Overall, our findings and those of others suggest that shame may have an important role in initiating ED psychopathology [ 26 , 27 , 29 , 70 , 73 , 74 ].…”
Section: Discussionsupporting
confidence: 82%
“…However, engaging in ED behaviors to cope with shame may eventually increase shame (e.g., regarding eating, shape and weight), setting up a vicious cycle [ 52 ]. Overall, our findings and those of others suggest that shame may have an important role in initiating ED psychopathology [ 26 , 27 , 29 , 70 , 73 , 74 ].…”
Section: Discussionsupporting
confidence: 82%
“…The themes of feeling misunderstood and having poor treatment experiences are consistent with other studies of international populations (Ma et al, 2021). These findings suggest that the consistency of these problems may need to be mitigated on a global level among intentional targeting through international associations (Nechita et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both body shame and general shame have been linked to eating disorders (e.g., Goss and Allan, 2009;Troop and Redshaw, 2012), body image disturbance (e.g., Duarte et al, 2015), and eating behaviors (e.g., Swan and Andrews, 2003). Indeed, a recent meta-analysis (Nechita et al, 2021) concluded that general shame, and body and eating shame in particular, are significantly positively associated with eating disorder symptoms. Most research studies in this area are cross-sectional, and thus further study of the link between different forms of shame (e.g., external, internal, body-focused, eating focused) and their impact on different types of eating disorder symptoms (e.g., dietary restriction, binge eating) using robust methods (e.g., longitudinal methods, ecological momentary assessment) is warranted (Nechita et al, 2021).…”
Section: Body Shamementioning
confidence: 99%
“…Indeed, a recent meta-analysis (Nechita et al, 2021) concluded that general shame, and body and eating shame in particular, are significantly positively associated with eating disorder symptoms. Most research studies in this area are cross-sectional, and thus further study of the link between different forms of shame (e.g., external, internal, body-focused, eating focused) and their impact on different types of eating disorder symptoms (e.g., dietary restriction, binge eating) using robust methods (e.g., longitudinal methods, ecological momentary assessment) is warranted (Nechita et al, 2021). In service of furthering research in this area, a number of shame measures are currently available in the literature.…”
Section: Body Shamementioning
confidence: 99%